Relational Distance and Epistemic Generosity: The Power of Detachment in Skeptical Ethnography. (November 2019) - Fine, Gary Alan
Much contemporary ethnography hopes to engage with a community to justify social critique. Whether from problem selection, interpersonal rewards, or a desire for exchange, researchers often take the "side" of informants. Such an approach, linked to "public ethnography, " marginalizes a once-traditional approach to fieldwork, that of the ethnographic stranger. I present a model of scholarly detachment and questioning of group interests. Drawing on my own experiences and those of members of the Second Chicago School, I argue for an approach in which an unaffiliated observer questions community interests, arguing that skepticism of local explanations can discover processes shared by other scenes and can develop transsituational concepts. While the ethnographer can be seduced into sharing a group's perspective, observational distancing can mitigate this. In an approach I label skeptical ethnography, the ethnographic stranger avoids partisan allegiance in the field and at the desk. Skepticism of local interests must be combined with an epistemic generosity that recognizes that all action, whether seemingly righteous or repellent, responds to an interaction order.